2014
DOI: 10.1186/bf03352239
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric investigations for the seismically active area in Northern Miyagi Prefecture, northeastern Japan

Abstract: The ELF-and the ULF-MT surveys were carried out in the northern part of Miyagi Prefecture, northeastern Japan. This area is one of the most seismically active areas in this region, where hypocenters of microearthquakes are distributed on a fault plane at depths from 2 to 16 km. The aim of the present study is to investigate the relationship between electrical resistivity structure and the hypocentral distribution of microearthquakes in the area. The calculated impedance tensor at each site has been obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…occurs below or adjacent to these zones in high-resistivity zones. Similar distributions of earthquakes on the boundary between high and low-resistivity regions have been observed for microearthquakes [Ichiki et al, 1999], swarms [Tank et al, 2003] and large earthquakes and their aftershocks [Eberhart-Phillips et al, 1990;Kasaya et al, 2002]. Takeda et al [1999] observed the occurrence of earthquakes at shallow depths in areas of low water saturation and high crack density surrounded by areas of high saturation.…”
Section: Discussionsupporting
confidence: 69%
“…occurs below or adjacent to these zones in high-resistivity zones. Similar distributions of earthquakes on the boundary between high and low-resistivity regions have been observed for microearthquakes [Ichiki et al, 1999], swarms [Tank et al, 2003] and large earthquakes and their aftershocks [Eberhart-Phillips et al, 1990;Kasaya et al, 2002]. Takeda et al [1999] observed the occurrence of earthquakes at shallow depths in areas of low water saturation and high crack density surrounded by areas of high saturation.…”
Section: Discussionsupporting
confidence: 69%
“…from 5 to 25 km, (Haberland et al, 2003;Sarma et al, 2004;Goto et al, 2005). Even though resolution decreases exponentially with depth, magnetotellurics is currently the most effective exploration tool to investigate the electrical properties of the crust at depths larger than 2-3 km (Ichiki et al, 1999;Ogawa et al, 2001;Ritter et al, 2003;Bedrosian et al, 2004;Tank et al, 2005).…”
Section: Electrical Resistivity Imaging Of a Seismic Region In Northern Baja California Mexicomentioning
confidence: 99%